INTEGRASI FUZZY MAMDANI BIOMEKANIKA DAN NIOSH: MANUAL MATERIAL HANDLING PENYARINGAN BUBUR KEDELAI - Johan Alfian Pradana; Rizki Puspita Dewanti; Catur Harsito; Saiful Rowi; Venus Khatta Salsabila (KAIZEN : Management Systems & Industrial Engineering Journal, 2022)
Manual material handling activities one of them is soy porridge filtration. Important research was conducted to provide interventions reviewed from aspects of NBM, biomechanics, NIOSH and fuzzy biomechanics to NBM as the purpose of this study. This research method takes a saturated sample of 24 respondents, observation and documentation regarding working posture, dissemination and withdrawal of NBM closed questionnaires, assessing biomechanics from the aspect of Fcompression with Fshear, and evaluating activities with NIOSH and integration of fuzzy Mamdani initiated fuzzification, inference, and defuzzification. The study showed that Fcompression 1117.05 N < 3400 N; Fshear of 613.4 N > 500 N were declared to be at risk. The dominant LI value may be at risk of 66.7% for 16 people. Traditional NBM complaints are very painful range 75%-100% at the waist (96%), hips (75%), buttocks (83%), right hands (79%), left thighs and right thighs (75%), left knee (92%), and right knee (100%). Traditional proof of biomechanics following fuzzy biomechanics against NBM, by 93.3%. This activity still has risks, both from traditional biomechanics, NIOSH, NBM, and fuzzy biomechanics to NBM. Therefore, appropriate intervention is needed from the aspect of facilities and work environment in the future